Provision of Public Services for Overall Well-being in the Municipality - Jēkabsone, Inga; Sloka, Biruta (Socialiniai tyrimai, 2015)
The aim of the paper is to present analysis of subjective well-being regarding municipality provided public services and its impact on overall well-being using the approved methodology.The main findings are as follow: in order to provide public services that meet the needs of the public, municipalities should involve the community in the decision-making process. Research into subjective well- being carried out in Salaspils municipality showed that well-being is directly affected by public services provided in the municipality.
Keywords: subjective well-being; municipality; citizen participation; public services